2005
DOI: 10.1152/ajpendo.00252.2004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced PDX-1 expression impairs islet response to insulin resistance and worsens glucose homeostasis

Abstract: In type 2 diabetes mellitus, insulin resistance and an inadequate pancreatic beta-cell response to the demands of insulin resistance lead to impaired insulin secretion and hyperglycemia. Pancreatic duodenal homeodomain-1 (PDX-1), a transcription factor required for normal pancreatic development, also plays a key role in normal insulin secretion by islets. To investigate the role of PDX-1 in islet compensation for insulin resistance, we examined glucose disposal, insulin secretion, and islet cell mass in mice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 62 publications
5
58
0
Order By: Relevance
“…1G). The functional ␤ cell defect observed in HF-fed Pdx1 ϩ/Ϫ mice is consistent with the impaired insulin secretion described in Pdx1 ϩ/Ϫ animals alone or in the context of genetic insulin resistance (4,16,17).…”
Section: Pdx1 ؉/؊ Mice Develop Diabetes In Response To Hfd-induced Insupporting
confidence: 78%
See 2 more Smart Citations
“…1G). The functional ␤ cell defect observed in HF-fed Pdx1 ϩ/Ϫ mice is consistent with the impaired insulin secretion described in Pdx1 ϩ/Ϫ animals alone or in the context of genetic insulin resistance (4,16,17).…”
Section: Pdx1 ؉/؊ Mice Develop Diabetes In Response To Hfd-induced Insupporting
confidence: 78%
“…While the role of Pdx1 in functional islet compensation appears unequivocal in genetic models of insulin resistance, these models provide discrepant results regarding its role in morphological ␤ cell compensation (16,17). To determine whether Pdx1 is required for normal ␤ cell mass expansion in response to HFDinduced insulin resistance, we measured pancreatic ␤ cell mass in Pdx1 ϩ/Ϫ and Pdx1 ϩ/ϩ mice fed HFD or NC for 5 months.…”
Section: Pdx1 Is Required For Compensatory ␤ Cell Mass Expansion In Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Pdx1 is an essential transcription factor for pancreas morphogenesis and postnatally is a key regulator of ␤-cell differentiation, maturation, and survival (31). It is required for the normal adaptive increase in ␤-cell mass and function to insulin resistance (32,33). Distal from Pdx1 is a network of genes that impact diverse aspects of ␤-cell signaling, mass, and function (34) including glucokinase with its well known regulatory effects on glycolysis, insulin secretion, and ␤-cell proliferation (35).…”
Section: Foxo1 and Ppar␥ Signaling In ␤-Cellsmentioning
confidence: 99%
“…FoxO1 is well poised to be a master transcriptional regulator over ␤-cell adaptive responses, as its expression and activity are influenced by numerous stimuli such as nutrient overload, growth factors, incretin hormones, and oxidative stress (13,14). Downstream from PPAR␥ is a network of genes that exert important regulatory control over prodifferentiation processes, incretin effects, glucose and mitochondrial fuel metabolism, and ␤-cell compensation to obesity and insulin resistance (13,27,32,33). We have shown that islet PPAR␥ and its target genes are hyperexpressed in nondiabetic insulin-resistant rats (present study and Refs.…”
Section: Foxo1 and Ppar␥ Signaling In ␤-Cellsmentioning
confidence: 99%